Fruit Development, pigmentation and biochemical properties of wax apple as affected by localized application of GA(3) under field conditions - Khandaker, M.M.; Boyce, A.N.; Osman, N.; Golam, F.; Rahman, M.M.; Sofian-Azirun, Mohd (2013)
This study investigated the effects of gibberellin (GA(3)) on the fruit development, pigmentation and biochemical properties of wax apple. The wax apple trees were rubbing treated with 0, 20, 50 and 100 mgGA(3)/l under field conditions. The localized application (rubbing) of 50 mg GA(3)/l significantly increased the fruit set, fruit length and diameter, color development, weight and yield compared to the control. In addition, GA(3) treatments significantly reduced the fruit drop. With regard to the fruit quality, 50 mg/l GA(3) treatment increased the juice content, K+, TSS, total sugar and sugar acid ratio of wax apple fruits. In addition, higher vitamin C, phenol, flavonoid, anthocyanin, carotene content, PAL and antioxidant activities were recorded in the treated fruits. There was a positive correlation between the peel colour and TSS content and between the PAL activity and anthocyanin formation in the GA(3)-treated fruit. It was concluded that rubbing with 50 mg/L GA(3) at inflorescence developing point of phloem once a week from the tiny inflorescence bud until the flower opening resulted in better yield and quality of wax apple fruits and could be an effective technique to safe the environment from excessive spray.